Pendampingan Pembiasaan Akhlak Sejak Dini Berdasarkan Kitab "Alala" Berbahasa Arab Di TPQ Sunan Ampel - Ghofur, M Abdul; Zakaria, Moh Sulthon (An-Nuqthah, 2024)
Imam Ghazali in the book Ihya 'Ulumuddin explains that morality is a trait, embedded in a person's soul with this trait an action can easily occur without the need to consider. In other words, morality is a person's condition that makes the person do something spontaneously. The purpose of the research itself focuses on children so that they can have noble morals starting from an early age. The methods used are teaching methods and real practice. While data collection uses observation, interviews and documentation. And the results obtained from this community service activity are very good, both in terms of data collection and the materials obtained for the children are very good as well as from the attitudes and morals they have